2019
DOI: 10.1115/1.4044779
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Measurement Approach for a Hydrogen Oxyfuel Combustor

Abstract: Higher shares of variable renewable generation have already raised the demand for energy storage and network services in the power sector. As this trend is expected to continue, the combination of these services in a large scale will be imperative toward a carbon-free power sector. A very promising way to perform this task without any additional emissions is through stoichiometric combustion of the electrolysis products (H2 and O2) in steam and the injection of the generated steam in a conventional steam cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…14. The previous studies [30,31] showed that increased steam dilution shifts the flame upstream and in radial direction. It transitions from a jet to a swirl-stabilized flame with a larger spread angle.…”
Section: Heat Transfer Through the Wallmentioning
confidence: 95%
See 1 more Smart Citation
“…14. The previous studies [30,31] showed that increased steam dilution shifts the flame upstream and in radial direction. It transitions from a jet to a swirl-stabilized flame with a larger spread angle.…”
Section: Heat Transfer Through the Wallmentioning
confidence: 95%
“…The lab-scale burner in the current work builds upon an experimentally well-characterized design of a swirl-stabilized H 2 /air burner [24][25][26][27], which was equipped with additional O 2 injectors. Preliminary results were reported by Schimek et al [28] and Tanneberger et al [29][30][31], who characterized the flow and flame behavior along with the combustion efficiency. In the current paper, these investigations are extended by an analysis of the heat transfer in the combustion chamber.…”
Section: Introductionmentioning
confidence: 98%
“…Fuel and/or oxidizer dilution can also be employed to control the reactivity and emissions formation of H 2 flames, as shown by Weiland and Strakey [12], who utilized excess N 2 for NO x control of a H 2 -air diffusion flame, and Tanneberger et al [13] who utilized steam dilution for stoichiometric operation of non-premixed H 2 -O 2 flames. However, both approaches imply air separation as part of the process, incurring an overall system efficiency penalty.…”
Section: Introductionmentioning
confidence: 99%